Coding of Multiple H.264 Video streams using SSIM as quality metric - Luís Teixeira (2008)
This paper proposes a joint rate control scheme for multiple video sequences coding based on H.264/AVC standard that produces uniform picture quality. Structural Similarly Information (SSIM), is assessed as a coding complexity of a video program measure regarding its perceptual quality. Initial results are presented and discussed.